EFFECT OF OCCLUSAL REDUCTION ON POSTOPERATIVE PAIN IN MULTIPLE VISIT ROOT CANAL TREATMENT - KUMAR, K; SARIM, S; HAMMAD, H; AHMED, M; IRFAN, F; NAFEES, H (Biological and Clinical Sciences Research Journal, 2022)
The study aimed to assess occlusal reduction’s effect on postoperative pain in multiple-visit root canal treatment. This randomized control trial was conducted at the Operative Dentistry & Endodontics Department, Baqai Dental College Karachi, from January 2021 to January 2022. A total of 110 patients fulfilling the inclusion criteria were included in the study. The patient was divided into two groups, Group A, occlusal reduction (OR) and Group B, no occlusal reduction (NOR). In group A, all occlusal contacts on the functional and non-functional cusps and the marginal ridges were reduced by 1 mm by a diamond bur in a high-speed handpiece and confirmed with articulating paper. No occlusal reduction was performed in group B patients. Patients were recalled after 24 hours and 7 days, and their pain level was recorded on VAS; at the same appointment, the root canal was completed, and the tooth was restored permanently. Pain level on the 7th day was taken as the study’s primary endpoint. The mean age of patients was 37.41±10.635, with a minimum age of 19 and a maximum of 59 years old. Female patients were 56% and 44%, male. There were two study groups’ OR 50% and NOR 50%. The tooth type included were 40% anterior and 60% posterior. Group A patients had reduced pain levels after 24 hours, with a significant difference of P=0.014 compared to group B patients. After 7 days of treatment, no significant difference was found in postoperative pain between both groups with P=0.533. Thus, it can be concluded from the study that the occlusive reduction may not be effective in reducing pain at the 7th postoperative days of multiple visit root canal treatment. Although a significant difference in pain levels was identified after 24 hours of therapy, patients in the occlusion reduction group reported less discomfort than those in the control group.